Kualitas Antioksidan Senyawa Fitokimia dan Karakteristik Kimia Kulit Buah Matoa (Pometia pinnata) yang Dikeringkan - Andriani, Mira; Nahrowi, Nahrowi; Jayanegara, Anuraga; Mutia, Rita; Syahniar, Theo Mahiseta (Jurnal Veteriner, 2020)
This study was aimed to examine the influence of drying temperature on phytochemical compounds and chemical characteristic of matoa ( Pometia pinnata ) peels. This study used a completely randomized design with the drying temperature treatments which was divided into P0 = freeze drying (control), P1 = 50 Ë% C, P2 = 60 Ë% C, and P3 = 70 Ë% C, each treatment was dried for 48 hours. Variables observed were phytochemical compounds, water content, ashes content, crude protein, crude fat, crude fiber, IC 50 , malondialdehide/MDA and phenol. This study used analysis of variance followed by Duncan Multiple Range Test when the results showed significance dierence. It was calculated through Statistical Package for Social Science (SPSS) version 21.0. The results showed that the drying temperature influenced water content and IC  50 . The phytochemical compounds of matoa peels were observed through qualitative screening included flavonoids, saponins, and tannins. The best results on the drying treatment of matoa peels was P1 (50 Ë% C) which presented 9.47±0.14% water content, 3.74±0.07% ashes content, 4.89±0.03% crude protein, 0.46±0.04% crude fat, 34.42±2.16% crude fiber, 30.92±10.25 IC 50 , 12.85±1.49 mg/g MDA, and 0.85±0.23% phenol.